Study of role of low molecular weight heparin in conjunction with conventional therapy in severe acute pancreatitis - Rojaramani Kumbha; Sobharani Bathena; Hari Babu Mekala Anand; Venkat Vineeth Amavasya (Asian Journal of Medical Sciences, 2022)
Background: Acute pancreatitis is a disease which has many etiologies. Each etiology seems to affect the pancreatic acinar cell in some way that results in premature activation and retention of potent proteolytic enzymes. Low molecular weight heparin (LMWH) is known to reduce the release the cytokines and inflammatory mediators and result in the improvement of microcirculation of pancreas. Aims and Objectives: The aim of the study was to determine the efficacy of LMWH therapy in patients with severe acute pancreatitis (SAP). Materials and Methods: Our research comprised of 100 patients who were randomly assigned to one of two groups: Conventional treatment for SAP (n=50) or conventional therapy +LMWH (n=50). All the data were statistically analyzed in SPSS software 15.0. Results: In both groups, the death rate was 2%, and 49 patients in each group were cured of their disease after therapy. The minimum hospital stay in the heparin group is 5 days, while the highest hospital stay is 17 days. In the conventional group, the minimum hospital stay is 4 days, and the maximum hospital stay is 21 days. Conclusion: For the treatment of SAP, LMWH is a straightforward, safe, effective, and cost- efficient technique. It is suitable for usage in any hospital. There was no significant improvement in the impact of traditional SAP therapy with LMWH, nor was there any reduction in SAP mortality. Renal problems were more prevalent among the patients than sepsis-related complications among the conventional group. It was, however, statistically insignificant.